(4n +2)π Huckel’s rule of Bn NnC(8-2n) H8 as anti-cancer heterocyclic systems - SamieiSoofi, Neda; Monajjemi, Majid (Revista de la Universidad del Zulia, 2020)
Replacing of Boron and nitrogen atoms in [8] annulene molecule help us for explaining the details of mentioned magnetic mechanism concerning the ring currents of the carbon disappearing in the isoelectronic azabora-hetero-cycles variants (Bn Nn C(8-2n) H82-,n=0,1,2,3 and4  The (4n+2)  systems aromatic on variants of BnNnC(8-2n) H8 (n=0, 1 ,2,3 and 4) via the localized orbital by considering   the current density induced have been studied. It has been predicted a four-electron dia-tropic (aromatic) ring current for (4n+2)  aza-bora-hetero-cycles variants of BnNnC (8-2n) H8(n=0,1 ,2,4) and a two-electron para-tropic (anti-aromatic) current for (4n) . HOMO and LUMO energies and also HOMO/LUMO overlapping in whole space have been calculated. Two forms can be considered, first the HOMO–LUMO transition leads to a para-tropic contribution, and second HOMO–LUMO+1 transitions to the dia-tropic contributions. In addition, the NICS and SNICS values confirm the amounts of aromaticity and anti-aromaticity in those rings.